Oxford History of India / edited by Percival Spear - "Smith, Vincent A." (Chennai, 2000)
As a reproduction of a historical artifact, this work may contain missing or blurred pages, poor pictures, errant marks, etc. Scholars believe, and we concur, that this work is important enough to be preserved, reproduced, and made generally available to the public. We appreciate your support of the preservation process, and thank you for being an important part of keeping this knowledge alive and relevant.
Keywords: "India-History, ancient"